The Prospect of Agribusiness in The Indonesian Economy - D.S. Priyarsono; H Siregar; D Bakce (Business and Entrepreneurial Review, 2005)
This paper argues that a strong agriculture sector is needed by the economy to rapidly grow. However, it is not sufficient. A strong agriculture sector can sustainably support the economic growth only if there are economic sectors that sufficiently demand commodities produced by the sector. The result of an analysis of Social Accounting Matrix (SAM) shows that agribusiness, or more specifically small and medium scale agriculture based industries, is the key for enhancing the performance of the economy. Agribusiness can also considerably improve the income of poor rural people and significantly create employment. Therefore, it would result in a better income distribution.